The Impact of Organizational Culture, Transformational Leadership and Job Satisfaction on the Performance of Private University Lecturers - ., Samsuri; Notosudjono, Didik; Sunaryo, Widodo (Journal of Ecohumanism, 2024)
There are still a small number of private universities that have achieved superior accreditation rankings. The main factor that can influence an institution’s accreditation ranking is lecturer performance. Research was conducted to examine the impact of organizational culture, transformational leadership and job satisfaction on lecturer performance. This research uses a survey method covering a population of 489 private university lecturers in Bogor. Data collection was carried out using a questionnaire which was analyzed using the SEM-PLS technique. Research findings show that organizational culture has a direct effect on lecturer performance and indirectly through job satisfaction, while transformational leadership has an indirect effect on lecturer performance through job satisfaction. The recommendation submitted to university leaders is to improve lecturer performance through strengthening the university’s organizational culture and increasing lecturer job satisfaction.